Randomized, controlled, double-blind trial of taranabant for smoking cessation - Morrison, Mary F.; Ceesay, Paulette; Gantz, Ira; Kaufman, Keith D.; Lines, Christopher R. (Psychopharmacologia, 2010)
Rationale It has been proposed that cannabinoid-1 receptor inverse agonists might be effective for smoking cessation. We evaluated this hypothesis with the cannabinoid-1 receptor inverse agonist taranabant. Methods Adults who smoked ≥10 cigarettes a day for >1 year and had an expired CO level of ≥10 ppm participated in a randomized, double-blind, 8-week, study of taranabant ( N = 159) or placebo ( N = 158). Taranabant was titrated from 2 mg once daily to 8 mg once daily. Patients received smoking cessation counseling. The primary efficacy endpoint was continuous abstinence, defined as no cigarettes assessed by daily patient self-report and verified by breath CO level (<10 ppm) and plasma cotinine test (<10 ng/ml), during the last 4 weeks of the 8-week treatment period. Results The percentage of patients achieving continuous abstinence was 7.5% for taranabant 2–8 mg and 6.3% for placebo (odds ratio = 1.2 [90% confidence interval (CI), 0.6, 2.5], P = 0.678). Change from baseline in body weight in the taranabant 2–8-mg group was −1.5 (90% CI, −1.8, −1.3) versus 0.6 kg (90% CI, 0.4, 0.9) in the placebo group. Compared to placebo, taranabant 2–8 mg was associated with an increased incidence of psychiatric-related adverse events (e.g., depression, 8.2% versus 2.5%, P = 0.048), gastrointestinal-related adverse events (e.g., nausea, 49.7% versus 19.0%, P < 0.001), and flushing/hot flash adverse events (10.7% versus 1.9%, P = 0.002). Conclusions Taranabant 2–8 mg did not improve smoking cessation and was associated with increased incidences of psychiatric-related, gastrointestinal-related, and flushing adverse events (ClinicalTrials.gov NCT00109135).